Associação do índice de massa corporal aos desfechos clínicos dos casos de COVID-19 - Trindade L.L.* (2021)
© The Authors.Objective: to analyze the association between Body Mass Index and the clinical outcomes of confirmed COVID-19 cases. Method: an epidemiological study conducted with secondary data from 618 confirmed COVID-19 cases, notified from March to December 2020 in a municipality from western Santa Catarina, Brazil. An inferential analysis was performed between Body Mass Index and several clinical and assistance-related aspects. Results: a significant association was found between Body Mass Index and the following symptoms: dyspnea (p=0.003), decreased appetite (p=0.004), runny nose (p=0.039) and diarrhea (p=0.029). There was also an association with previous comorbidities (p=0.000) and worse saturation mean values (p=0.00). Obese individuals presented more chances of: hospitalization in a ward (p=0.027); hospitalization in an Intensive Care Unit (p=0.002); and evolution to death (p=0.00). Conclusion: the need to implement effective educational actions for the prevention and treatment of obesity is evidenced, focusing on quality of life and mitigation of the clinical deterioration of this population in the face of pathologies such as COVID-19.